Recipient Factors Associated With Graft Detachment of a Subsequent Eye in Sequential Descemet Membrane Endothelial Keratoplasty. Issue 10 (October 2020) - Kim, Kyeong Hwan; Tijunelis, Marius A.; Zhou, Yunshu; Musch, David C.; Hood, Christopher T.; Tannen, Bradford L.; Mian, Shahzad I.
Abstract : Purpose: To evaluate the recipient factors associated with graft detachment in the subsequent eye of patients who underwent sequential Descemet membrane endothelial keratoplasty (DMEK). Methods: A retrospective, consecutive case series with 158 eyes of 79 patients who underwent DMEK surgeries in both eyes between October 2013 and April 2019 for treatment of Fuchs endothelial dystrophy. The main outcome measure was the presence of graft detachment (any amount of detachment) at postoperative 1 week in the subsequent eye. Preoperative, intraoperative, and postoperative factors were evaluated for association with graft detachment. Results: Of 79 patients (158 eyes) with a mean follow-up of 11.7 ± 8.4 months, 18 patients (36 eyes) developed graft detachment in both eyes 1 week postoperatively. The risk of detachment in the subsequent eye was increased when the first eye had any amount of detachment [odds ratio = 2.8; 95% confidence interval (CI) = 1.1–7.3; P = 0.037]. When the first eye had a clinically significant detachment (>30% detached), the risk of detachment occurring in the subsequent eye was greater (odds ratio = 15.7; 95% CI = 1.8–134.5; P = 0.012). This risk of graft detachment in the subsequent eye increased 33% for every 5% increase in the detachment percentage in the first eye (odds ratio = 1.3; 95% CI = 1.1–1.6; P = 0.008). Conclusions: The presence of graft detachment after DMEK increases the risk of graft detachment in subsequent DMEK in the contralateral eye. Modification in perioperative care and surgical technique in the contralateral eye, such as a larger gas bubble, use of SF6 20%, and combining cataract surgery, may be needed when graft detachment occurs after DMEK in the first eye.